Analysis of factors affecting motor vehicle tax revenue (South Sumatra Province 2006-2020) - Basri, M. Hasan; Isnurhadi, Isnurhadi; Widiyanti, Marlina; Adam, Mohamad (International research journal of management, IT and social sciences, 2021)
This study aims to determine the effect of changes in investment, consumption, DGFB per capita, inflation on motor vehicle tax revenues in South Sumatra Province. Motor vehicle tax revenues were sampled with the research period 2006-2020. The research used the multiple linear regression method. The results showed that changes in investment, consumption, and inflation did not significantly affect motor vehicle tax revenues in South Sumatra in 2006-2020. Meanwhile, DGFB per capita has a significant positive effect on motor vehicle tax revenues in South Sumatra in 2006-2020.